2020
DOI: 10.3233/bmr-181479
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of an upper cervical spine traction-manipulation program in patients with cervicogenic dizziness: A case series study

Abstract: BACKGROUND: Damage on the somatosensory system could cause sensation of dizziness, a condition known as cervicogenic dizziness (CD). Manual physical therapy has shown beneficial effects, relieving the symptoms of cervicogenic dizziness. However, the effect of upper cervical spine manipulation is unknown, as this is a technique that respects the International Federation of Orthopedic Manipulative Physical Therapists (IFOMPT) safety criteria. OBJECTIVE: To assess the effects of upper cervical spine traction-mani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…Hidalgo-García et al [3] and Malo-Urriés et al [1] found an increase in the flexion-rotation test when applying a mobilization in C0-1 segment. Carrasco-Uribarren et al [50] evaluated the flexion-rotation test, and applied a protocol of traction manipulation in the resting position in C0-1, C1-2 and C2-3 segments, obtaining similar results to those observed in this study.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Hidalgo-García et al [3] and Malo-Urriés et al [1] found an increase in the flexion-rotation test when applying a mobilization in C0-1 segment. Carrasco-Uribarren et al [50] evaluated the flexion-rotation test, and applied a protocol of traction manipulation in the resting position in C0-1, C1-2 and C2-3 segments, obtaining similar results to those observed in this study.…”
Section: Discussionsupporting
confidence: 82%
“…C1-2 rotation is limited by the alar ligament system and occipital, and C2 are the main bony attachments of alar ligaments. Some authors have proposed that C0-1 [1,3] and/or C2-3 [50] dysfunction may inhibit the normal rotational mobility of C1-2 [53]. The MT + E group received a tailored manual therapy treatment according to the C0-1 and C2-3 dysfunction of each patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes would explain the presence of contralateral changes in sensitivity to pressure pain in the current study. However, despite these findings, it seems clear that changes in the treated areas seem to be more substantial than those in distant areas [54][55][56].…”
Section: Changes In Sensory and Motor Outcomesmentioning
confidence: 88%
“…2Dd ), were combined with cervical exercise in all sessions ( Kaltenborn, 2009 , 2012 ; Krauss & Evjenth, 2009 ; Hidalgo García et al, 2016 ; Malo-Urriés et al, 2017 ). Manipulations were applied in the direction of traction, with the head in a neutral position ( Carrasco-Uribarren et al, 2020 ). A maximum of two trials at each level were performed on each side, yielding 2–6 thrusts per each visit ( Reynolds et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%